Augmented Reality (AR) Based Approach in Nursing Education: A Preliminary Project - Ahmad Marzuki, Maziah; Hashim, Harwati (International Journal of Engineering and Technology, 2018)
Lecturers aware that learning deepens, not just through reading and listening, but also through creating and interacting. In normal practices, nursing students will utilize the Microsoft words application or produce normal poster to complete their task or assignment for submission. However, problems persist when the students need to do revision where they need to refer to posters or giant book that they had created. The students also had to bring them everywhere and this hinder them from referring to the project to enhance their learning. Therefore, in this project, Augmented Reality (AR) was used as a tool for students to create tasks given by lecturer. This approach was applied to nursing students at PPUKM for the learning of softs skills. In this approach, AR allows the students to engage in and create learning experiences of their own. Lecturers and students can use this open source tool to essentially bring their learning to become more meaningful. Students could also obtain the information related to soft skills easier anytime anywhere. The AR based approach also encouraged students to become creators of their own learning as well as increasing their interest in learning.Â Â